COMPARATIVE DESCRIPTION OF LINEAR AND ANGULAR INDEXES OF NORMAL AND ARTIFICIALLY DEFORMED SKULLS OF PEOPLE FROM ARCHAEOLOGICAL EXCAVATIONS OF UPPER SALTOV, CHERSONESES, TEPE-KERMEN AND LOWER DON - Fedoryshcheva, V.O. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Linear and angular indexes of facial and cerebral departments of 98 normal and artificially deformed human skulls from the archaeological excavations of Upper Saltov, Chersoneses, Tepe-Kermen and Lower Don were compared. The linear and angular values on X-ray films between points: Ba, B, V, L, N, O, Op, Or, Pr, S, Fca were measured.  The mean value (M), standard quadratic deviation (sd), error of middle (m), the variation coefficient (C) were determined. Statistical analysis between groups was carried out using nonparametric the Mann-Whitney test and the criterion of Wald-Wolfovyts and the Student’s t-test criterion. Indices of low variability in all skulls were determined. There are no reliable distinctions of craniometric indexes of skulls from Tepe-Kermen and Chersoneses. Reliable differences between groups of normal skulls from all of the studied regions, between the skulls with artificial deformation and normal skulls into one region and between the skulls with artificial deformation from different regions are exposed.